2017
DOI: 10.3906/sag-1601-198
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with dendritic cell-based vaccine and anti-CD69 antibody enhances antitumor efficacy in renal cell carcinoma-bearing mice

Abstract: IntroductionRenal cell carcinoma accounts for 4% of all malignant tumors (1) and has an incidence of about 8-9 persons per 100,000 each year, which is increasing (2). There is no obvious symptom in the early stage of this cancer. As a result, approximately 25%-30% of patients exhibit tumor metastasis at first diagnosis and lose the opportunity for surgery (3). Although patients with primarily localized renal cell carcinoma can be successfully treated by partial or radical nephrectomy, one third of cases will s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…4C , 4E and 4F . Consistent with our results, some researchers found that anti-CD69 antibody can potentiate antitumor efficacy of dendritic cell-based vaccine, which is considered to be associated with increased T-cell proliferation and activity ( Wei et al, 2017 ). Others also found that CD69 deficient mice challenged with prostate carcinoma showed greatly reduced tumor growth and prolonged survival, which be due to the enhanced anti-tumor response of lymphocytes and increased lymphocytes in local ( Esplugues et al, 2003 ).…”
Section: Discussionsupporting
confidence: 92%
“…4C , 4E and 4F . Consistent with our results, some researchers found that anti-CD69 antibody can potentiate antitumor efficacy of dendritic cell-based vaccine, which is considered to be associated with increased T-cell proliferation and activity ( Wei et al, 2017 ). Others also found that CD69 deficient mice challenged with prostate carcinoma showed greatly reduced tumor growth and prolonged survival, which be due to the enhanced anti-tumor response of lymphocytes and increased lymphocytes in local ( Esplugues et al, 2003 ).…”
Section: Discussionsupporting
confidence: 92%
“…75 Tumor lysate and tumor-derived exosomes are also used to activate DCs, and the results show that they can induce T cell activation and proliferation. 76,77 Moreover, it avoids the limitation of antigen selection and is accepted widely by patients. 78,79 All of these approaches have been successful and are simple and cheap.…”
Section: Dc-based Cancer Vaccinesmentioning
confidence: 99%
“…The results suggested that DCs pulsed with LY6E peptide antigen strongly matured and activated T cells . Tumor lysate and tumor-derived exosomes are also used to activate DCs, and the results show that they can induce T cell activation and proliferation. , Moreover, it avoids the limitation of antigen selection and is accepted widely by patients. , All of these approaches have been successful and are simple and cheap. We can pulse DCs with antigens that can induce an efficient immune response or combine different antigens from the same tumor to stimulate DCs to improve DC activation.…”
Section: Dc-based Cancer Vaccinesmentioning
confidence: 99%
“…Wei et al . [31] applied DC-based vaccine and anti-CD69 antibody treatment in murine RCC and reported that anti-CD69 antibody increased antitumor efficiency of DC-based vaccine and caused significant decrease in tumor volume and significant increase in T-cell proliferation and activity.…”
Section: Dendritic Cell Vaccinesmentioning
confidence: 99%